Anti-Tumor Effects of Vespa bicolor Venom on Liver Cancer: In Vitro and In Vivo Studies - Yong-Hua Wu; Feng Xiong; Zheng-Wen Ou; Jing-An Wang; Jing Cui; Lin Jiang; Wen-Jian Lan (Toxins)
Despite the popular belief in the anti-tumor properties of Vespa bicolor venom (VBV), there is limited scientific evidence to support this claim. This study is the first to examine the anti-tumor effects of VBV on liver cancer, both alone and in combination with cisplatin (DDP), through in vitro and in vivo experiments. In vitro experiments evaluated VBV and its combination with DDP on HepG2 cell proliferation, invasion, migration, and apoptosis. Animal studies examined the tumor-suppressive effects, safety (hepatotoxicity and nephrotoxicity), and immune impact of these treatments in tumor-bearing mice. VBV monotherapy significantly inhibited the growth of HepG2 cells by suppressing their proliferation and invasion and induced apoptosis in vitro. Notably, low VBV concentrations significantly promoted the proliferation of normal liver cells (L-02), suggesting a hepatoprotective effect. In vivo, VBV monotherapy enhanced immune function and exhibited tumor suppression comparable to DDP monotherapy but did not induce significant liver or kidney damage. In addition, VBV combined with DDP synergistically enhanced the anti-tumor effects of DDP, compensating for its limited apoptosis-inducing activity and insufficient enhancement of immune function. Initial studies have shown the strong potential of VBV as an anti-liver-tumor drug, highlighting its unique clinical value.